2021
DOI: 10.3390/nu13030834
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Dietary Patterns and Inflammatory Markers during Pregnancy: A Systematic Review

Abstract: Elevated inflammation in pregnancy has been associated with multiple adverse pregnancy outcomes and potentially an increased susceptibility to future chronic disease. How maternal dietary patterns influence systemic inflammation during pregnancy requires further investigation. The purpose of this review was to comprehensively evaluate studies that assessed dietary patterns and inflammatory markers during pregnancy. This review was guided by the Preferred Reporting Items for Systematic Review and Meta-Analyses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 92 publications
1
17
0
Order By: Relevance
“…Furthermore, according to the regression analyses of the present study, pregnancy-induced inflammation appears to be mostly associated with ppBMI and the progression of pregnancy itself. Overall, our results regarding associations between diet and inflammation are inconsistent, which is in line with the observations of a D r a f t page 15 recent systematic review (Yeh et al, 2021). Most of the 17 studies included in that review showed associations between pro-inflammatory markers and dietary patterns like the pro-/anti-inflammatory diet and the Mediterranean diet.…”
Section: R a F Tsupporting
confidence: 65%
“…Furthermore, according to the regression analyses of the present study, pregnancy-induced inflammation appears to be mostly associated with ppBMI and the progression of pregnancy itself. Overall, our results regarding associations between diet and inflammation are inconsistent, which is in line with the observations of a D r a f t page 15 recent systematic review (Yeh et al, 2021). Most of the 17 studies included in that review showed associations between pro-inflammatory markers and dietary patterns like the pro-/anti-inflammatory diet and the Mediterranean diet.…”
Section: R a F Tsupporting
confidence: 65%
“…Obesity is one of the most important modifiable risk factors for development of pregnancy metabolic complications, and therefore, diet modification is also of utmost importance. Our study showed that increasing total fat intake by 1 g is associated with a 0.25 kg increase in maternal body weight, a 0.28 kg/m 2 increase in maternal BMI, and a 0.29 mg/L increase in serum CRP levels, all of which pose an increased risk for developing metabolic complications in pregnancy [ 32 , 33 ]. There appears to be mixed results in the literature regarding fat intake and resulting inflammatory profiles and risk for metabolic complications in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is a proinflammatory molecule secreted from adipose deposits and increased levels can lead to metabolic complications such as GDM and HDP. Therefore, decreasing the levels of IL-6 may be beneficial in improving these risks [ 33 ]. Moosavian et al, in a meta-analysis of randomized control trials in non-pregnant adults of varying health statuses, documented that high consumption of dairy products showed a significant reduction in inflammatory markers such as IL-6 [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the link between diet and systemic inflammation is well established, fewer studies have examined this relationship in pregnancy, and particularly, on offspring inflammation. A recent systematic review summarized the evidence on associations between diet and maternal inflammation in pregnancy [47]. Despite inconsistent data, the authors reported that maternal diet with higher animal protein and cholesterol and lower fiber were associated with higher inflammation biomarkers (IL-6, IL-8, CRP or TNF-α) [47].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review summarized the evidence on associations between diet and maternal inflammation in pregnancy [47]. Despite inconsistent data, the authors reported that maternal diet with higher animal protein and cholesterol and lower fiber were associated with higher inflammation biomarkers (IL-6, IL-8, CRP or TNF-α) [47]. In Project Viva, a cohort of 1808 mother-child dyads in Massachusetts and a pro-inflammatory maternal diet (measured with the dietary inflammatory index (DII) [48], was positively associated with maternal systemic inflammation, measured by second trimester maternal serum CRP (β: 0.08 mg/L per 1-unit increase in maternal DII, 95% CI: 0.02, 0.14) [48].…”
Section: Discussionmentioning
confidence: 99%